End of life care for people with dementia: The views of health professionals, social care service managers and frontline staff on key requirements for good practice. - Richard Philip Lee; Claire Bamford; Marie Poole; Emma McLellan; Catherine Exley; Louise Robinson (PLoS ONE)
Background Evidence consistently shows that people with advanced dementia experience suboptimal end of life care compared to those with cancer; with increased hospitalisation, inadequate pain control and fewer palliative care interventions. Understanding the views of those service managers and frontline staff who organise and provide care is crucial in order to develop better end of life care for people with dementia. Methods and findings Qualitative interviews and focus groups were conducted from 2013 to 2015 with 33 service managers and 54 staff involved in frontline care, including doctors, nurses, nursing and care home managers, service development leads, senior managers/directors, care assistants and senior care assistants/team leads. All were audio recorded and transcribed verbatim. Participants represented a diverse range of service types and occupation. Transcripts were subject to coding and thematic analysis in data meetings. Analysis of the data led to the development of seven key themes: Recognising end of life (EOL) and tools to support end of life care (EOLC), Communicating with families about EOL, Collaborative working, Continuity of care, Ensuring comfort at EOL, Supporting families, Developing and supporting staff. Each is discussed in detail and comprise individual and collective views on approaches to good end of life care for people with dementia. Conclusions The significant challenges of providing good end of life care for people with dementia requires that different forms of expertise should be recognised and used; including the skills and knowledge of care assistants. Successfully engaging with people with dementia and family members and helping them to recognise the dying trajectory requires a supportive integration of emotional and technical expertise. The study strengthens the existing evidence base in this area and will be used with a related set of studies (on the views of other stakeholders and observations and interviews conducted in four services) to develop an evidence-based intervention.